Evolutions of tidal flats and tidal creeks under geomorphological and eco-hydrological controls:A case study in the Yellow River Delta, China - Teng Su; Yan Li; Hongyuan Shi; Pengjun Yin; Tao Lu; Qing Wang; Qiuyu Song (CATENA, 2026)

Exploring interactive and nonlinear effects of key factors on intercity travel mode choice using XGBoost - Xiaowei Li; Lanxin Shi; Yang Shi; Junqing Tang; Pengjun Zhao; Yuting Wang; Jun Chen (Applied Geography, 2024)

Efficient decolorization of melanoidin in raw molasses wastewater by thermophilic esterase in actual extreme conditions - Zedong Zhang; Wanting Hu; Qiuyue Xie; Yuezhe Shi; Yutong Zhao; Yaxin Deng; Jiaxin He; Xia Wu; Yu Zhang; Wenqi Zhang; Pengjun Liu; Hao Yang; et al. (Bioresource Technology, 2023)

A new xylanase from Streptomyces megasporus DSM 41476 with high yield of xylobiose - Pengjun Shi; Zhenhua Qiu; Yingguo Bai; Tiezheng Yuan; Huoqing Huang; Xia Pan; Peilong Yang; Wei Zhang; Bin Yao (World Journal of Microbiology and Biotechnology, 2012)

An acidic β-mannanase from Penicillium sp. C6: gene cloning and over-expression in Pichia pastoris - Hongying Cai; Pengjun Shi; Huoqing Huang; Huiying Luo; Yingguo Bai; Peilong Yang; Kun Meng; Bin Yao (World Journal of Microbiology and Biotechnology, 2011)

Two Types of Phytases (Histidine Acid Phytase and β-Propeller Phytase) in Serratia sp. TN49 from the Gut of Batocera horsfieldi (Coleoptera) Larvae - Rui Zhang; Peilong Yang; Huoqing Huang; Pengjun Shi; Tiezheng Yuan; Bin Yao (Current Microbiology, 2011)

Diversity, abundance and characterization of ruminal cysteine phytases suggest their important role in phytate degradation - Huoqing Huang; Rui Zhang; Dawei Fu; Jianjie Luo; Zhongyuan Li; Huiying Luo; Pengjun Shi; Peilong Yang; Qiyu Diao; Bin Yao (Environmental Microbiology, 2011)
Summary A novel class of cysteine phytase showing ability to degrade phytate has recently been isolated from rumen bacteria. To expand our knowledge of this enzyme class, a total of 101 distinct cysteine phytase gene fragments were identified from the ruminal genomic DNA of Bore goats and Holstein cows, and most of them shared low identities (

A novel xylanase, XynA4-2, from thermoacidophilic Alicyclobacillus sp. A4 with potential applications in the brewing industry - Jianshe Wang; Yingguo Bai; Pengjun Shi; Huiying Luo; Huoqing Huang; Jun Yin; Bin Yao (World Journal of Microbiology and Biotechnology, 2011)

Effects of the antibiotic growth promoters flavomycin and florfenicol on the autochthonous intestinal microbiota of hybrid tilapia (Oreochromis niloticus ♀ × O. aureus ♂) - Suxu He; Zhigang Zhou; Yuchun Liu; Yanan Cao; Kun Meng; Pengjun Shi; Bin Yao; Einar Ringø (Archives of Microbiology, 2010)

A new xylanase from thermoalkaline Anoxybacillus sp. E2 with high activity and stability over a broad pH range - Jianshe Wang; Yingguo Bai; Peilong Yang; Pengjun Shi; Huiying Luo; Kun Meng; Huoqing Huang; Jun Yin; Bin Yao (World Journal of Microbiology and Biotechnology, 2010)

Characterization of a chromosomal segment showing xylanolytic activity from the symbiotic Sphingobacterium sp. TN19 - Junpei Zhou; Kun Meng; Peilong Yang; Pengjun Shi; Yaru Wang; Huiying Luo; Bin Yao (World Journal of Microbiology and Biotechnology, 2010)

Phytase production by fermentation of recombinant Pichia pastoris in monosodium glutamate wastewater - Yingguo Bai; Peilong Yang; Yaru Wang; Pengjun Shi; Huiying Luo; Kun Meng; Bo Wu; Bin Yao (World Journal of Microbiology and Biotechnology, 2009)

Gene cloning, expression and characterization of an α-galactosidase from Pedobacter nyackensis MJ11 CGMCC 2503 with potential as an aquatic feed additive - Xiaodan Liu; Kun Meng; Yaru Wang; Pengjun Shi; Tiezheng Yuan; Peilong Yang; Huiying Luo; Yingguo Bai; Bin Yao (World Journal of Microbiology and Biotechnology, 2009)

A thermophilic and acid stable family-10 xylanase from the acidophilic fungus Bispora sp. MEY-1 - Huiying Luo; Jiang Li; Jun Yang; Hui Wang; Yuhui Yang; Huoqing Huang; Pengjun Shi; Tiezheng Yuan; Yunliu Fan; Bin Yao (Extremophiles, 2009)